Copper-promoted aerial oxidation of benzothiadiazines: access to benzothiadiazine S-oxide heterocycles1. Issue 5 (7th February 2015) - Clark, Ewan R.; Hayward, John J.; Leontowicz, Bryce J.; Anwar, Muhammad U.; Pilkington, Melanie; Rawson, Jeremy M.
<x xml:space="preserve">Abstract</x> Aerial oxidation of benzothiadiazines selectively affords the corresponding benzothiadiazine S-oxides in the presence of Cu2+ ions. Structural studies reveal that the S-oxide appears to be a strong hydrogen-bond acceptor.